1999
DOI: 10.1051/analusis:1999107
|View full text |Cite
|
Sign up to set email alerts
|

Determination of mercury in estuarine sediments by flow injection-cold vapour atomic absorption spectrometry after microwave extraction

Abstract: Abstract.A flow injection-cold vapour atomic absorption spectrometric (CVAAS) method was developed for the determination of mercury at trace level in estuarine sediments using sodium tetrahydroborate (III) as reductant. The mercury was solubilized with nitric acid in closed vessels and microwave oven heating. Instrumental and operational conditions (volume and concentration of reagents, reaction time, etc.) were optimized. The effect of several ions on the analytical signal was also studied; no interferences w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This technique has many significant advantages in comparison with the conventional batches procedure, as lower consumption of sample solutions and reagents, simplicity for mercury determination, high sensitivity and relative freedom from interference. 22 The peak area signals were measured and the mercury content of the samples was calculated against the mercury standard curves. All samples for this study were analyzed in three replicates.…”
Section: Mercury Determinationmentioning
confidence: 99%
“…This technique has many significant advantages in comparison with the conventional batches procedure, as lower consumption of sample solutions and reagents, simplicity for mercury determination, high sensitivity and relative freedom from interference. 22 The peak area signals were measured and the mercury content of the samples was calculated against the mercury standard curves. All samples for this study were analyzed in three replicates.…”
Section: Mercury Determinationmentioning
confidence: 99%
“…20,21 This technique is based on the chemical reduction of mercury to elemental Hg, followed by measurement of mercury vapor absorption at 253.7 nm. 18,20 The aim of this work is the development of a method for the direct determination of Hg II in ethanol fuel samples by CV-AAS without further sample pretreatment. channel peristaltic pump equipped with Tygon and polyethylene tubes that carry the sample through a reaction coil, where it is acidified and mixed with a suitable reductant.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the most employed method for Hg determination in different matrices, such as biological tissues, water, sediments, blood, and foods, is CV-AAS, because it is a very sensitive and relatively low cost. , This technique is based on the chemical reduction of mercury to elemental Hg, followed by measurement of mercury vapor absorption at 253.7 nm. , …”
Section: Introductionmentioning
confidence: 99%
“…12,15 Sodium chloride present in the sample matrix was reported to affect the mercury signal using CVAAS. 16 It was well reported that complete decomposition of the organic matter in plant material and others was not observed using a lowpressure closed-vessel microwave digestion system; 6,17 also organic matter present in the sample digest can affect the analytical signals of Hg by CVAAS.…”
Section: Effect Of Matrix Interferencementioning
confidence: 99%
“…[8][9][10] The total mercury in sediments and biological samples were determined using offline microwave digestion with flow-injection CVAAS. 11,12 The aim of this work was to develop a simple, rapid, sensitive and high sample throughput method for the determination of mercury in botanical and CPM samples. The developed method uses two different types of closed vessels for microwave digestion with sodium tetrahydroborate and hydroxylammonium chloride as a reductant in the final determination by CVAAS.…”
mentioning
confidence: 99%